PENGARUH SERTIFIKASI GURU TERHADAP KINERJA GURU PADA SD NEGERI DUKUH MENANGGAL I SURABAYA - Fidah Indrayanti; Achmad Daengs GS; Rina Dewi (Jurnal Mahasiswa Manajemen dan Akuntansi, 2022)
This study aims to determine (1) the effect of teacher certification on teacher performance at the Dukuh Menanggal I State Elementary School (SD) Surabaya; and (2) the difference in the performance of teachers at SD Negeri Dukuh Menanggal I Surabaya who are certified and not certified. The research population that will be taken is 30 teachers at SD Negeri Dukuh Menanggal I Surabaya in 2022. The independent variable in this study consists of 4 indicators. The dependent variable in this study is teacher performance. The method used to collect data in this study is a questionnaire method (questionnaire). Testing data collection tools using validity and reliability tests. Hypothesis test using multiple linear regression analysis, normality test, and different test. The hypotheses in this study are (1) H1. There is an effect of teacher professional certification on the performance of religious teachers at SD Negeri Dukuh Menanggal I Surabaya; and (2) H2. There is a difference in the performance of teachers at SD Negeri Dukuh Menanggal I Surabaya who are certified and not certified. Based on the results of the research and discussion, the following conclusions can be drawn: (1) Teacher professional certification has no effect on the performance of religious teachers at SD Negeri Dukuh Menanggal I Surabaya; and (2) there is no difference between the performance of certified and uncertified teachers at SD Negeri Dukuh Menanggal I Surabaya.